Simulation of Loading Traffic in a High-Speed Grinding Aggregates - P.E. Vaitekhovich; V.S. Frantskevich; P.S. Grebenchuk; D.N. Borovskii (Механика машин, механизмов и материалов, 2014)
The basic problems of modern technics and technology grinding materials are explored, key areas of the industry are identified. It is shown that mathematical modeling of material flow in the grinders to optimize their design parameters at the design stage. The examples of the mathematical description of the flow of the material presented in the form of a granular medium, in the working bodies of middle-speed, strike-centrifugal, centrifugal ball mills. The results of calculations of the main technological parameters of these machines with the help of developed models are produced. Conclusions on the possibility of using mathematical models in the design of centrifugal grinding method comprising units of various designs are made.